Proximal analysis of chihua pumpkins accessions in the Yucatán Peninsula - Ruiz García, José Luis; Villalobos-González, Antonio; Cetzal Ix, William Rolando; López-Hernandez, Mónica Beatriz; Rangel-Fajardo, María Alma; García-Sandoval, José Ángel (Revista Mexicana de Ciencias Agrícolas, 2020)
The objective of the work was to determine the content of protein and dry matter in the seed (%PROTSEMC, %MATSSEMC), shell (%PROTCASC, %MATSCASC) and pulp (%PROTPULC, %MATSPULC), and percentage of carbohydrates (%CARBCA), fat (%GRASCRU) and ash (%CENCA) in the seed of six accessions of chihua pumpkins (Cucurbita argyrosperma Huber), native to the Yucatán Península. The accessions evaluated were: Becal, Edzna, Pixoyal, Chihua local, CACAO and CECHET. The sowing was carried out in June 2017 in Pocyaxum, Municipality of San Francisco de Campeche, Mexico, in a randomized block design with three repetitions, analysis of variance and mean comparisons were performed with the Tukey test (p≤ 0.05). The experimental unit consisted of three rows of 6 m in length, separated at 2.40 m and 1.25 m between plants. For the determination of proteins, the Kjeldahl method was used, and following the process described in AOAC (2000). The CECHET accession showed higher (p≤ 0.05) %PROTESEMC, %PROTCASC, %MATSSEMC and %MATSPULC with 33.6, 14.4, 64.9 and 4.29%, respectively. Edzna, Becal, Local Yucatan presented 3.8% PROTPULC less (p≤ 0.05) compared to the CECHET, CACAO and Pixoyal accessions. Edzná presented higher (p≤ 0.05) % GRASCRU with 45.3%. Becal, presented the highest (p≤ 0.05) %CARBCA with 34.7%. The % MATSCASC of the CACAO accession (12.5% MATSCASC) exceeds (p≤ 0.05) those obtained in the rest of the accessions. There were no differences (p≤ 0.05) for the %CENCA. The accession that stood out was CECHET, with the highest percentage of protein in seed, peel, pulp and dry matter in seed and pulp. Accessions with nutritional intake for consumption were identified that can be an alternative for preparing different foods.